2016
DOI: 10.3389/fnana.2015.00169
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Microstructure is Associated with Auditory and Tactile Processing in Children with and without Sensory Processing Disorder

Abstract: Sensory processing disorders (SPDs) affect up to 16% of school-aged children, and contribute to cognitive and behavioral deficits impacting affected individuals and their families. While sensory processing differences are now widely recognized in children with autism, children with sensory-based dysfunction who do not meet autism criteria based on social communication deficits remain virtually unstudied. In a previous pilot diffusion tensor imaging (DTI) study, we demonstrated that boys with SPD have altered w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(111 citation statements)
references
References 42 publications
6
101
1
3
Order By: Relevance
“…To varying degrees, all children with SPD struggle to properly modulate incoming sensory information, making it difficult to function in the same way as their unaffected peers [1,4143]. The observed behavioral and neural findings support the idea that a subset of the SPD population face greater cognitive control deficiencies compared to TDC, which acts as an additional impediment in their daily lives.…”
Section: Discussionmentioning
confidence: 89%
“…To varying degrees, all children with SPD struggle to properly modulate incoming sensory information, making it difficult to function in the same way as their unaffected peers [1,4143]. The observed behavioral and neural findings support the idea that a subset of the SPD population face greater cognitive control deficiencies compared to TDC, which acts as an additional impediment in their daily lives.…”
Section: Discussionmentioning
confidence: 89%
“…These modalities contain 10, 11, 13, 8, 8, and 10 items, respectively. Previous studies have demonstrated relationships between brain morphology and modality-specific sensory behaviors measured by caregiver report questionnaires or structured assessments [Chang et al, 2014[Chang et al, , 2016Owen et al, 2013;Pryweller et al, 2014] as well as how to evaluate modality-specific sensory processing using the Adolescent/Adult Sensory Profile [Demopoulos et al, 2015]. Based on these findings, the present study summed the items within each modality to generate six modalityspecific subscales for the visual, auditory, touch, taste/ smell, movement, and activity level modalities.…”
Section: Participantsmentioning
confidence: 95%
“…We conjectured that a sensory-first phenotype, in this case AOR, allows for a more parsimonious identification of key neural tracts. Indeed, in our previous work based on parent report and a broad inclusion criteria for sensory processing dysfunction, we found decreased FA in children with SPD in the posterior body and isthmus of the corpus callosum, the left posterior thalamic radiations (PTR), left PCR, and the posterior aspect of the left SLF [27]. Here, for children with AOR, the PCR, CGC, and SLF tracts showed decreased FA.…”
Section: Discussionmentioning
confidence: 56%
“…For structural Diffusion Tensor Imaging (DTI) analysis, we included 39 boys from UCSF who successfully completed direct sensory assessment and neuroimaging assessment (ASD, n=13 (age 11 years +/− 2), SPD, n=8 (age 11 years +/− 1) and TDC, n=18 (age 12 years +/− 1)). This cohort has been previously described in Chang et al, 2016 [27]. Due to a small sample size in the tactile domain, we constrained the DTI analysis to the auditory domain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation